Clinical features, risk factors, and outcomes of neonatal invasive candidiasis: a 20-case study series from a tertiary neonatal critical care unit in Oman - Basem Abdelhadi; Mujtaba Al Ajmi; Hilal Al Hashami; Manal Al Rawahi (Italian Journal of Pediatrics)
Abstract Background One of the well-known causes of morbidity and mortality in the neonatal population is invasive candidiasis. In neonatal critical care units, candida sepsis is now the third most frequent cause of late-onset sepsis. The objective of this research was to determine the prevalence of related risk factors, clinical traits, and results related to invasive candidiasis in the neonatal intensive care unit (NICU) at the Royal Hospital in Oman. Methods A case–control retrospective analysis of 20 newborns admitted between January 2006 and December 2020 to the neonatal intensive care unit at Royal Hospital. In terms of gestational age, birth weight, and date of birth, cases and controls were matched. Results There were 60 infants in all- 20 cases and 40 controls. The two groups'demographics, including age, sex, and weight, were comparable. The case group compared to the control group had a mean gestational age of 32.2 ± 6.1 weeks against 32.2 ± 5.7 weeks and a mean birth weight of 1978 ± 1202 grammes against 1930 ± 1040 grammes, respectively. A total of 14,820 newborns were admitted to the NICU during the study period, with 20 cases of candidemia, representing an incidence of approximately 1.3 per 1000 admissions. Seventy-five percent of the isolated species were Candida albicans. Sixty-five percent of the instances happened in the second and third week of life. Compared to the control group, the case group's mean NICU stay was longer. Several risk factors, including young maternal age, the presence of a central line, invasive mechanical ventilation, total parenteral nutrition, prolonged hospital stay, necrotizing enterocolitis, abdominal surgeries for congenial intestinal malformations and cardiac surgeries for congenital heart diseases, were found to be related with an elevated risk for invasive candidiasis using univariate analysis. In the case group, the overall mortality rate was 45%, but in the control group, there was no death in the cohort. Conclusion The following factors were linked to an elevated risk of invasive candidiasis in this case series: total parenteral nutrition, prolonged hospital stay, central line presence, prematurity, abdominal and cardiac surgeries. Those with risk characteristics should be highly suspected for neonatal candidiasis, particularly if their stay in the NICU is longer than seven days. Antifungal prophylaxis should be taken into consideration for these newborns, and presumed antifungal medication should be started as soon as possible.